2021
DOI: 10.1093/scan/nsab014
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing humanity: dehumanization predicts neural mirroring and empathic accuracy in face-to-face interactions

Abstract: Dehumanization is the failure to recognize the cognitive and emotional complexities of the people around us. While its presence has been well documented in horrific acts of violence, it is also theorized to play a role in everyday life. We measured its presence and effects in face-to-face dyadic interactions between strangers and found that not only was there variance in the extent to which they perceived one another as human, but this variance predicted neural processing and behavior. Specifically, participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…It is correlated with trait measures of empathic concern ( DiGirolamo et al. , 2019 ) and inversely correlated with dehumanization ( Simon and Gutsell, 2021 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is correlated with trait measures of empathic concern ( DiGirolamo et al. , 2019 ) and inversely correlated with dehumanization ( Simon and Gutsell, 2021 ).…”
mentioning
confidence: 99%
“…The mounting evidence from the literature suggests that mu suppression is linked to inferences about others from low-level visual motor cues such as photographs and possibly low-level auditory cues (see Simon and Gutsell, 2021 , for an exception). But the identification and discrimination tasks used in these previous experiments fall short of the complexity of everyday affective reasoning, and it is not clear whether or how these representations contribute to higher-level reasoning about others’ affective states, especially in naturalistic contexts (e.g.…”
mentioning
confidence: 99%
“…Consequently, such malleability of social perceptions can result in different forms ranging from no (perceived) to exaggerated intergroup differences. So far, literature has consistently demonstrated that harsh intergroup differentiation (ingroup vs. outgroup) produce a range of biased intergroup responses: ingroup favoritism (Tajfel, Billig, Bundy, & Flament, 1971;Otten & Moskowitz, 2000); memory biases (Park & Rothbart, 1982); fundamental attribution error (Pettigrew, 1979); linguistic biases (Maass, Salvi, Arcuri, & Preprint: THE PROCESS OF BECOMING "WE" Semin, 1989), dehumanization (Demoulin, et al, 2009;Simon & Gutsell, 2021) and ultimately less prosocial intergroup behavior (Voci, 2006).…”
Section: Social Categorizations: Us Vs Themmentioning
confidence: 99%
“…An individual’s tendency to use animalistic dehumanization decreases the more the individual’s spatial and temporal features resemble the self (Hasson and Frith, 2016; Northoff and Huang, 2017; Scalabrini et al, 2019) and the more dissimilar those features are to those of animals, as suggested by electroencephalographic μ suppression in face-to-face dyadic interactions (Simon and Gutsell, 2021). In contrast, increased anthropomorphism, or extending human features to other animals or objects, may potentially increase animalistic dehumanization by blurring the human–animal boundary (Hortensius and Cross, 2018; Rottman et al, 2021).…”
Section: “Animalistic” Dehumanizationmentioning
confidence: 99%